PENGEMBANGAN PROGRAM PENDIDIKAN KETERAMPILAN DI PONDOK PESANTREN - Kharis (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2021)
Islamic boarding schools as one of the non-formal educational institutions has a very important role in improving the quality of human resources in Indonesia. One of the efforts to improve the quality of students / santri is by providing skills education programs. So that santri are expected to solve their life problems in the future. The results showed the development of skills education programs in Islamic boarding schools can be implemented in by: (1) developed by Islamic boarding school academic programe, (2) developed by Islamic boarding school extracurricular activities, (3) developed by a community, (4) developed by habituation, and (5) developed by seminars and training. The skills program that can be developed in Islamic boarding schools are: (1) personal skills, (2) academic skills, (3) social skills, and (4) vocational skills. With these efforts, the boarding school is expected to develop and prepare the skills of santri to continue their life after leaving the boarding school.Key Words: development, skills education, Islamic boarding school